The low concentrations of hydrogen peroxide reduce biofilm formation - Ghadah Mohommed Saleh (World Journal of Experimental Biosciences, 2019)
Biofilm formation is considered a serious problem that faces the physician in treating infectious diseases associated with medical devices. The present study aims to highlight the effect of hydrogen peroxide (H2O2) on biofilm formation by bacteria and yeasts. The current study confirms the anti-biofilm effect of H2O2 on the biofilm formed by bacteria and yeast. The effects of H2O2 on biofilm formation were against the ability of a microorganism to attach to the surface by the effect on either the appendages or the mechanisms of attachment, also it was found that the effect on biofilm can be explained by the effect on the microorganism growth. The current study highlighted the future prospect of using H2O2 by increasing the effectiveness of common antibiotics against high-resistance bacteria by increasing the ways of entering antibiotics by forming pores in the biofilm mass and the microorganism cells.
Keywords: Biofilm, Extracellular Polymeric Substances (EPS), H2O2, Reactive Oxygen Species (ROS).